AWARENESS AND UTILIZATION OF LIBRARY RESOURCES AND SERVICE AMONG THE USERS OF TALUK PUBLIC LIBRARIES IN KOLAR DISTRICT: A STUDY. - Naregal, Jyoti G; L B, Pallavi (International Journal of Research -GRANTHAALAYAH, 2025)
The present research paper examine that overall distributed and collected among the Users of the Taluk Public Library Distributed 150 questionnaires 130(86.67%) are received among them. Followed by 95(73.07%) of them are males and 35(26.92%) are female, 15(11.5%), 16-25 age group covers 30(23.07%), 26 to 35 group contains 15(11.53%), 36-45 group covers 12(9.23%), 46-55 group covers 52(40%), and 55 above age covers 6(4.61%), 70(53.5%) of the respondents are Degree, 40(30.7%) of the respondents are Post graduates, 10(7.69%) of the respondents are PUC and SSLC students, 48(36.92%) of the respondents are married, and 82(63.07%) of respondents are Unmarried. This concludes that the majority of the users are unmarried of 82 (63.07%), 98(75.38%), Twice a week is 12(9.23%), Weekly is 2(1.53%), Monthly visit is 10(7.69%), and rarely is 8(6.15%).